Student satisfaction and academic performance at UNI : Evaluation with the 6 Qs model - Ordóñez Mercado, Alipio Francisco (2009)
The vertiginous growth in the number of universities in our country has raised certain doubts about the quality of the university teaching process. Government agencies have set the standards for the accreditation of university studies, which cannot be improved if we do not know what students perceive. This study proposes the 6 Qs model to know the dimensions of student satisfaction and finds that there is a relationship of approximately 10% with academic performance, clearly establishing its multidimensional character, and that Research and basic infrastructure are the most dissatisfied indicators and need to be improved as a priority.